Population ecology of bagworm (Metisa plana) at different strata in oil palm plantation / Mohd Zulkarnain Ja'afar - Ja'afar, Mohd Zulkarnain (Faculty of Plantation and Agrotechnology, 2015)
Elaeis guineensis commonly known as oil palm is one of the major industry in plantation that are growth in Malaysia. The oil palm yield can be influence by many factors. One of them is bagworm. The importance and nature of injury we must know about bagworm are bagworm damaging stage is the larva, because the larva will eat plant leaves. In south Asia, Metisa plana (Lepidoptera: Psychidae) is an important defoliator of oil palm. The experiment was conducted at Felda Gunung Besourt 6, at Sungkai, Perak. The study location was chosen as through history is one of the most serious attack by bagworm and easy to access. The higher for total means are at the Lower strata with 76.9 individuals, followed by Middle strata (63) and lastly at the Upper strata (26.9). Bagwonn on ten oil palm tree and six weeks tend to ate at the Middle strata and Lower strata. At the Lower strata and Middle strata are have higher the total means of bagwonn with 76.9 and 63.0 individuals.